2014
DOI: 10.1111/jfpp.12275
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Treatment of Fish in Two Different Solutions-Artificial Neural Network Model

Abstract: Osmotic treatment of fish (Carassius gibelio) was studied in two osmotic solutions (ternary aqueous solution -S1 and sugar beet molasses -S2) at three temperatures (20, 35 and 50C) and atmospheric pressure. The aim was to examine the influence of type and concentration of used hypertonic agent, temperature and immersion time on the water loss, solid gain, dry mater content, water activity and minerals content (Na, K, Ca and Mg). During experiments, the maximum mineral content has been obtained using S2 soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…and a w value of 0.887 ± 0.010 (Ćurčić et al . ; Lončar ). While, in comparison to the osmotically dehydrated pork meat, dehydrated chicken had achieved slightly lower process response values, since dehydrated pork meat had achieved DMC of 62.16 ± 0.44%; WL of 0.4950 ± 0.0029 g/g i.s.…”
Section: Resultsmentioning
confidence: 99%
“…and a w value of 0.887 ± 0.010 (Ćurčić et al . ; Lončar ). While, in comparison to the osmotically dehydrated pork meat, dehydrated chicken had achieved slightly lower process response values, since dehydrated pork meat had achieved DMC of 62.16 ± 0.44%; WL of 0.4950 ± 0.0029 g/g i.s.…”
Section: Resultsmentioning
confidence: 99%
“…A significant lack of fit generally demonstrates that the model failed to represent the data in the experimental domain at which points were not included in the regression All SOP models had an insignificant lack of fit tests, which implies that all the models represented the data satisfactorily. The coefficient of determination, r 2 , is defined as the ratio of the explained variation to the total variation and is explained by its magnitude [43]. The r 2 values for FRAP (0.580), ABTS (0.492), DPPH (0.782), HPMC (0.979), MRAP (0.930) and FC (0.955) were very good and show the good fit of the model to experimental results.…”
Section: Response Surface Methodology (Rsm)mentioning
confidence: 99%
“…Dietary fibre ingredients and u-3 fatty acids could be added into conventional pasta to increase health benefits. The results showed that the dietary fibre function is the prevention of constipation, reduction of bowel transit time and reduction in the risk of colorectal cancer, lowering of blood cholesterol and regulation of blood glucose levels for diabetes management (Brennan & Cleary, 2005;Drusch & Mannino, 2009;Faivre and Bonithon-Kopp, 1999;Filipovi c & Filipovi c 2010;Filipovi c, Filipovi c, & Filipovi c, 2010;Filipovi c, Popov, & Filipovi c, 2008;Kolanowski, 2005). Inulin, as a glucofructan, consists of a mixture of oligomers and polymers containing 2 to 60 b 2-1 linked D e fructose molecules.…”
Section: Introductionmentioning
confidence: 96%